2015
DOI: 10.1186/s12891-015-0502-9
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban does not impair fracture healing in a rat femur fracture model: an experimental study

Abstract: BackgroundThe prescription of the oral anticoagulant rivaroxaban to prevent thromboembolic episodes associated with orthopaedic surgery has dramatically increased since it was introduced. Rivaroxaban is beeing prescribed although recent in-vitro studies revealed that it impaired osteoblast metabolism. In this study we analysed the effect of rivaroxaban on fracture healing in a rat femur fracture model.MethodsFemur fractures were created by a 3-point-bending device in 48 Wistar rats and subsequently stabilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 22 publications
3
19
0
6
Order By: Relevance
“…Preclinical studies have come to differing conclusions. Klüter et al (16) (17). Rivaroxaban inhibited the stimulation of cell proliferation, energy metabolism, alkaline phosphatase specific activity and mRNA modulation by a variety of hormones, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Preclinical studies have come to differing conclusions. Klüter et al (16) (17). Rivaroxaban inhibited the stimulation of cell proliferation, energy metabolism, alkaline phosphatase specific activity and mRNA modulation by a variety of hormones, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…The new orally administrated anticoagulant drugs are equally effective and safe with LMWH but there are also some indications that they do not affect bone healing 23,24 . Kluter et al in an experimental study found that Rivaroxaban does not impair fracture healing in a rat femur fracture model after analysis of callus by histology and the quality of the callus by CT scans 12 . Recent work from Israel 11 showed no delay in bone healing as well as no affection of cell mineralization after the administration of high doses of Rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism for this effect of LMWH on bone biology is not clear, it seems that LMWH reduce cancellous bone volume, affecting osteoblasts and human mesenchymal stromal cells in the early stages of bone healing 21,22 . In addition, LMWH seem to bind the vascular endothelium which disrupts callus vascular assembly and also increase the hematoma and cytotoxic effects on cells of the medullary callus 12,23 . The new orally administrated anticoagulant drugs are equally effective and safe with LMWH but there are also some indications that they do not affect bone healing 23,24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations